2021
DOI: 10.1111/lam.13468
|View full text |Cite
|
Sign up to set email alerts
|

High concentration of sodium chloride could induce the viable and culturable states of Escherichia coli O157:H7 and Salmonella enterica serovar Enteritidis

Abstract: In the present study, Escherichia coli O157:H7 and Salmonella enterica serovar Enteritidis were transferred into Luria–Bertani medium without NaCl (LBWS) and adjusted to various pHs (4, 5, 6 and 7) with lactic acid containing 0·75, 5, 10 and 30% NaCl, and stored at 25°C until the bacterial populations reached below detectable levels on tryptic soy agar (TSA). Although E. coli O157:H7 and S. Enteritidis did not grow on TSA when incubated in LBWS with 30% NaCl for 35 and 7 days, more than 60 and 70% of the bacte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 28 publications
0
4
0
Order By: Relevance
“…Interestingly, Song and colleagues discovered that more than 60% of VBNC E. coli O157:H7 were present in E. coli that had been incubated with 30% NaCl for 35 days when using SYTO 9 staining. 25 In addition, Spiekermann et al have designed a straightforward and highly sensitive staining assay that uses Nile Red to detect poly (3-hydroxybutyric acid) and other polyhydroxyalkanoic acids (PHAs) situated directly in growing bacterial colonies. 31 Researchers could estimate the presence of PHAs in viable colonies during growth experiments and to make a robust distinction between PHA-negative and PHA-positive strains.…”
Section: Culture-based Methodsmentioning
confidence: 99%
“…Interestingly, Song and colleagues discovered that more than 60% of VBNC E. coli O157:H7 were present in E. coli that had been incubated with 30% NaCl for 35 days when using SYTO 9 staining. 25 In addition, Spiekermann et al have designed a straightforward and highly sensitive staining assay that uses Nile Red to detect poly (3-hydroxybutyric acid) and other polyhydroxyalkanoic acids (PHAs) situated directly in growing bacterial colonies. 31 Researchers could estimate the presence of PHAs in viable colonies during growth experiments and to make a robust distinction between PHA-negative and PHA-positive strains.…”
Section: Culture-based Methodsmentioning
confidence: 99%
“…Decreased expression of virulence genes leads to reduced toxicity of bacteria, which is a typical characteristic that appears after pathogenic bacteria entering into the viable but non‐culturable (VBNC) state. Many studies have shown that under unfavorable conditions, such as low temperature, dryness, nutrient deficiency, antibiotics, and extreme pH, some non‐sporogenic microorganisms would enter the VBNC state for survival (Bai et al., 2019; Cervero‐Arago et al., 2019; Debnath & Miyoshi, 2021; Jameelah et al., 2018; Jayeola et al., 2022; Phung et al., 2022; Progulske‐Fox et al., 2022; Song & Lee, 2021; Yang et al., 2022; Zhong & Zhao, 2019; Zhong et al., 2019). Besides virulence‐related genes, other researchers found that the expression of some adhesion‐related genes also decreased after nisin treatment at sub‐inhibitory concentrations, while the expression of biofilm‐related genes increased.…”
Section: Bacteriostatic Mechanisms Of Nisinmentioning
confidence: 99%
“…Different salt concentrations, however, exert rather complicated influences on the survival of E. coli during pickle fermentation (Li et al, 2021;Song & Lee, 2021). Lower salt concentration, for example, was found to lead to faster growth of E. coli initially but reduced its survival time by promoting acid production (Chi et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Fermentation with low salt concentration (1%–3%) for pickle making has drawn increasing attentions (Lee et al, 2021; Rothwell et al, 2022)for reducing the risk of health disorders (Gao et al, 2022) and lessening the pollution of fresh water (Perez‐Diaz et al, 2015). Different salt concentrations, however, exert rather complicated influences on the survival of E. coli during pickle fermentation (Li et al, 2021; Song & Lee, 2021). Lower salt concentration, for example, was found to lead to faster growth of E. coli initially but reduced its survival time by promoting acid production (Chi et al, 2016).…”
Section: Introductionmentioning
confidence: 99%